The effect Pengaruh Kemampuan Akademik dan Semangat Kerja Terhadap Proses Penyelesaian Skripsi Pada Mahasiswa FEB UNIPA - Merlin Raru; Sylvia Margareth Sabarofek; Dirarini Sudarwadi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2021)
This study aims to determine the effect of academic ability and work spirit on the thesis completion process. This type of research uses quantitative research. The population in this study were students of the Faculty of Economics and Business class 2015 and 2016 with a total of 154 students and the sample taken was 61 respondents. Data were collected using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that: (1) academic ability partially has no effect on the thesis completion process, (2) work morale partially does not affect the thesis completion process, (3) academic ability and work spirit simultaneously have no effect on the completion process. thesis.